Representasi Kisah Pewayangan pada Iklan Sirup Marjan Versi “Baruna” dalam Perspektif Estetika Postmodern - Haryadi, Toto (DeKaVe, 2023)
The competition in advertising is so tight that causes over communication. Every company does different way, one of them is through creative advertising by highlighting the local culture which is rarely exposed by other companies. This has been done by the producer of Marjan syrup which is famous for presenting creative advertisements and received positive appreciation, especially the version of "Baruna the Guardian of the Ocean" as Marjan's advertisement with the highest viewers on YouTube. Behind the creativity from a technical point of view, it uses high-quality Computer Generated Imagery (CGI), this advertisement has become a topic of research because of its aesthetic concept, which adapts the story of the puppet character Baruna in a modern packaging and undergoes changes from the original story. The research used qualitative methods, supported by observation and literature studies of similar research, and continued with content analysis methods to discover postmodern aesthetics. The result is that there are some postmodern aesthetic concepts embedded in this advertisement, through changes in wayang stories according to the current era. This research is expected to be a reference in similar studies from another point of view.